Festival, Media and Images of Tourist Destination - Example of a Contemporary Croatian Urban Festival - Kelemen, Petra (2008)
The paper focuses on a contemporary Croatian urban festival - Špancirfest (Festival of Street Strollers). It stresses the interdependence of the festival and the media discourse, and the strong connection between the festival and the town(especially the town’ s tourist image constructed through the festival).